Structural characterization of antibiotic self-immunity tRNA synthetase in plant tumour biocontrol agent - Shaileja Chopra (Nature Portfolio, 2016)
The bacterium Agrobacterium radiobacter K84 secretes an antibiotic that is transported into the plant pathogen A. tumefaciensand processed into the toxin TM84. Here, the authors identify a mechanism whereby the antibiotic-producing microbe resists its own toxin.